Research on Heritage Conservation and Development of Chinese Ancient Towns and Historic Districts Based on Knowledge Graph Analysis - Wu Jin; Hiroatsu Fukuda (Buildings, 2025)
Historic districts of ancient towns serve as significant carriers of historical and cultural heritage while also being popular tourist destinations. Within the context of urbanization and organic renewal, the protection and development of historic districts have become crucial research topics. This study collects literature from the Web of Science database and applies manual screening to ensure relevance to the research theme. Using CiteSpace as an analytical tool, the study conducts a visual analysis from multiple perspectives, including keywords, writing time, authors, centrality, keyword clustering analysis, and timeline visualization. By constructing a knowledge graph, this research explores the key pathways and knowledge nodes in the organic renewal of spatial environments in historic districts of ancient towns. Based on literature clustering, the study categorizes research into four major aspects: heritage conservation, cultural and tourism development, spatial planning and design, and environmental enhancement. Based on this, universal strategies for the cultural and tourism development of historic districts in ancient towns are proposed. The research focus shifts from emphasizing cultural heritage preservation to the integrated development of culture and tourism. In the spatial development of historic districts, everyday life scenes should be incorporated while new technologies should be utilized to enhance environmental comfort. This paper summarizes the current research frontiers in this field and proposes future research trends, providing valuable references for scholars in related areas.